Biomarker Indicator of Abnormal Physiological Process - Begum, Ghousia (IntechOpen, 2018)
This book investigates the emerging use of biomarkers as a diagnostic tool for the identification of patients with an abnormal condition or as a tool for staging the extent of disease, as an indicator of disease prognosis. Chapters in Part I focus on biomarkers for cancer, including breast cancer and pancreatic cancer, as well as circulating microRNA profiling in cancer biomarker discovery. Chapters in Part II focus on biomarkers of other diagnoses/diseases, including sepsis, childhood renal diseases, pulmonary diseases, Alzheimer's, leishmaniasis, and heart failure. This book investigates the emerging use of biomarkers as a diagnostic tool for the identification of patients with an abnormal condition or as a tool for staging the extent of disease, as an indicator of diseases prognosis. The book is of considerable importance for a broad range of people including researchers, clinicians, and university students.